Stimulating Creativity in Children Aged 5-6 Years Through the Use of Natural Materials - Andi Ningsi Nabila; Siti Misra Susanti; Marwah Marwah (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
This study aims to stimulate early childhood creativity through the use of natural materials in educational activities at TK Mulya Mandiri, Wakuli Village, Kapontori District. The background of this research is the low level of children’s creativity caused by limited variation in learning media and minimal use of the surrounding environment as a learning resource. A qualitative approach with Participatory Action Research (PAR) was employed, conducted in two cycles consisting of planning, action implementation, observation, and reflection. Subjects were early childhood students at TK Mulya Mandiri. Data collection techniques included observation, interviews, documentation, and field notes, with descriptive qualitative data analysis. Results show that using natural materials in learning activities improves children’s creativity. Activities included stringing natural materials, collages from leaves and seeds, ecoprint, leaf spraying, stamp art using potatoes, and butterfly mosaics from flowers. These activities made children more active, creative, and enthusiastic. Improvement was seen in indicators of fluency, flexibility, originality, and elaboration. In Cycle I, most children were in the “starting to develop” category, while in Cycle II, the majority reached “developing as expected” and “very well developed” categories. Thus, using natural materials is effective in stimulating early childhood creativity and can serve as a reference for teachers in developing creative and innovative learning.